Spiritual Capital and Market Identity: The Symbolism of Ungku Saliah in Minang-Pariaman Trade Strategies - Ahmad Bisyri Abd.Shomad; Mumin Roup; Restia Gustiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
This study explores the socio-religious phenomenon of displaying photos of Ungku Saliah, a charismatic cleric from Pariaman, by Minangkabau traders in various Indonesian regions. The research aims to understand the motivations behind this practice and how religious symbols are integrated into modern trade strategies. Using a qualitative ethnographic approach, data were collected between 2021 and 2024 through field observations and in-depth interviews with traders in Pariaman, Padang, and South Tangerang. The findings reveal that the display of Ungku Saliah’s photo functions as a form of